Early motor developmental milestones and health outcomes in preadolescent children - Card, Madison R.; Raine, Lauren; Zimmerman, Emily; Schott, Nadja; Hillman, Charles H. (Frontiers in Developmental Psychology, 2024)
IntroductionThe prevalence of depression and anxiety in children has risen in recent years, while childhood obesity and sedentary behavior continue to be a major public health concern. Existing evidence suggests early motor development and locomotor experiences contribute to psychosocial and physical development. By further understanding the far-reaching effects of early motor development, early life interventions aimed at preventing physical and mental health adversity may benefit from investigating early motor developmental milestones (MDM) attainment. The current study is the first to assess the longitudinal association between parent-reported gross MDM timing with objective measures of mental health, cardiorespiratory fitness (CRF), subcutaneous abdominal (SAAT), and visceral adipose tissue (VAT) outcomes later in childhood.MethodIn total, 131 children aged 8–11 years (46% female) were recruited. The parents of these children reported the age of attainment for five MDMs: holding their head unsupported, rolling over, sitting unsupported, standing, and walking independently. The study encompassed a comprehensive assessment, including measures of mental health, CRF (VO2 max), body–mass index (BMI), SAAT, and VAT. Data were analyzed using multiple stepwise linear regressions, adjusting for demographic and parental factors in Step 1 and including each MDM individually in Step 2.ResultsOur findings indicated earlier rolling over and walking were associated with higher CRF during preadolescence. Earlier rolling over was also linked to healthier BMI and lower levels of VAT, lower levels of trait anxiety, and fewer symptoms of depression.ConclusionThis study provides further evidence with potential clinical implications that parent-reported MDM age of attainment is related to later preadolescent physical and mental health. The age at which a child first rolls over emerges as a particularly predictive factor for various preadolescent health outcomes, highlighting the multi-finality of MDM timing in understanding developmental trajectories.